The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2196/mhealth.8256
|View full text |Cite
|
Sign up to set email alerts
|

An mHealth App for Self-Management of Chronic Lower Back Pain (Limbr): Pilot Study

Abstract: BackgroundAlthough mobile health (mHealth) interventions can help improve outcomes among patients with chronic lower back pain (CLBP), many available mHealth apps offer content that is not evidence based. Limbr was designed to enhance self-management of CLBP by packaging self-directed rehabilitation tutorial videos, visual self-report tools, remote health coach support, and activity tracking into a suite of mobile phone apps, including Your Activities of Daily Living, an image-based tool for quantifying pain-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 28 publications
3
49
0
Order By: Relevance
“…Other studies suggest less of a benefit from tailoring messages to maintain users’ interest; despite a low attrition rate of 22% at 4 months and 1 year in two studies, respectively, an app and health counseling did not reduce hemoglobin A1c levels between the intervention and usual care groups [ 17 , 30 ]. In addition, self-management skills and the ability to contact health professionals were found to increase engagement, while users’ feedback input improved usability of apps and enhanced user experiences for daily self-reports [ 17 , 19 ]. Classifying different types of users may be important in improving long-term engagement.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies suggest less of a benefit from tailoring messages to maintain users’ interest; despite a low attrition rate of 22% at 4 months and 1 year in two studies, respectively, an app and health counseling did not reduce hemoglobin A1c levels between the intervention and usual care groups [ 17 , 30 ]. In addition, self-management skills and the ability to contact health professionals were found to increase engagement, while users’ feedback input improved usability of apps and enhanced user experiences for daily self-reports [ 17 , 19 ]. Classifying different types of users may be important in improving long-term engagement.…”
Section: Resultsmentioning
confidence: 99%
“…This paper presented the design and use of the HCF-based telehealth program for patients with CHF. Similar to other pilot studies [20], we focused on user perceptions and experience because user perspective was the most important dimension in the development phase of telehealth projects [21,22]. According to the interviews of participants, their family members, and physicians, they were generally satisfied with the service.…”
Section: Discussionmentioning
confidence: 99%
“…A mobile health (mHealth) intervention is one approach to encourage proactive self-management skills and improve well-being to reduce the development of secondary complications and health care costs [18-20]. Several studies have evaluated the benefit of mHealth in managing chronic conditions [21-24], and the results indicated that mHealth could provide better adherence to intervention regimens, such as compliance with taking medications, and better self-tracking capability to support self-management. Therefore, mHealth showed promise in promoting health-related activities.…”
Section: Introductionmentioning
confidence: 99%